The Influence of Business Ties and National Culture on Foreign-Subsidiary Capability Building in an Emerging Market. Issue 4 (1st October 2016) - Lee, Soo-Hoon; Bao, Shuji 'Rosey'; White, George O.
ABSTRACT: This study investigates the effects of formal and informal business ties on foreign-subsidiary capability-building activities. Data from 175 foreign subsidiaries in the Philippines shows that formal business ties are negatively related to capability building, whereas informal business ties are positively related to capability building. The authors also find that foreign-subsidiary home country assertiveness positively affects the positive relationship between informal business ties and capability building. These results indicate that in an emerging market, foreign-subsidiary capability building varies by the type of business ties being employed by a foreign subsidiary and that home-country assertiveness influences these outcomes.